Weaponising threat intelligence data. Issue 8 (August 2017) - Major, Tom
Abstract : In a world built on a hyper-connected business ecosystem, a breach in any area of that system can have a significant impact on a company's bottom line and – what's worse – damage its reputation. This can be seen in the recent headlines on major cyber-attacks spreading across countries and heavily impacting organisations we all rely on. The desire for access to company data is leading to a surge in increasingly sophisticated cyber-attacks. And the quantity of threat data being generated means the normal methods of observing and reporting can no longer keep pace. To fend off cyber-criminals, organisations need to be able to spot certain behaviours and characteristics that attackers exhibit when planning an attack. As the industry continues to refine predictive cyber-security tools, our ability to track malware and hone in on cyber-criminals' movements will become even more effective at stopping cyber-attacks, argues Tom Major of Level 3 Communications.